The relationship between romantic and prenatal maternal attachment: The moderating role of social support. (22nd April 2020) - Ponti, Lucia; Smorti, Martina; Ghinassi, Simon; Tani, Franca
Abstract : The aim of this study was to examine the relationships between three types of maternal attachment bonds: anxious romantic, avoidant romantic and prenatal. The moderating role of perceived social support is also analysed. Ninety‐one pregnant women in or near their thirtieth week of gestation ( M = 29.59; SD = 4.57) were recruited, all of whom completed a series of questionnaires to assess the quality of their romantic and prenatal attachment bonds and their levels of perceived social support. The results reveal that both anxious and avoidant romantic attachments were significantly associated with low levels of maternal prenatal attachment. Moreover, the level of social support perceived during pregnancy moderated the relationship between anxious and prenatal attachments but had no effect on avoidant romantic and prenatal attachments. Our discussion of these findings considers the emotional and behavioural characteristics of various forms of insecure romantic attachments. Overall, the data highlight the relevance of the quality of intimate close relationships on maternity experiences and women's caregiving abilities.